Penerapan Komunikasi SBAR (Situation, Background, Assesment, Recomendation) Oleh Perawat Di Rumah Sakit Pusri Palembang - Sutrisari Sabrina Nainggolan (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
SBAR communication is a framework for effective communication techniques provided for health workers in communicating the patient's condition. Nurses have the opportunity to discuss with other health teams. Mistakes in communicating SBAR will have undesirable effects on patients. This study aims to explore the application of SBAR (Situation, Background, Assessment, Recomendation) communication by nurses at the Pusri Palembang Hospital. Qualitative descriptive research design with a phenomenological approach. The research was conducted from April 2020 to May 2020. There were five participants in this study using purposive sampling technique, with the criteria of a minimum S1 nursing education, a work period of more than two years, had attended effective communication training, and were able to apply SBAR communication. The method of collecting information is carried out by in-depth interviews using the zoom meeting application. The data analysis used the Collaizi approach. From the research results obtained three themes, namely the experience of implementing SBAR communication, the contents of the SBAR report, and the barriers to SBAR communication. The results of this study can be used as material for monitoring and evaluating the performance of medical personnel at the Pusri Palembang Hospital related to the application of SBAR communicati